Ahimsa as a Universal Ethical Principle: Gandhian Perspective - Maji , Avijit (Revista Review Index Journal of Multidisciplinary, 2024)
This paper critically investigates the idea of ahimsa as a universal ethical standard within Mahatma Gandhi’s philosophical framework. Gandhi reinterprets ahimsa as a dynamic and all-encompassing moral philosophy based on truth (satya), love, and moral responsibility, despite its origins in ancient Indian religious traditions. The study examines the philosophical underpinnings of Gandhian ahimsa, highlighting its constructive and proactive nature as a catalyst for both social and personal development. It examines the inherent connection between ahimsa and satyagraha in more detail, showing how moral persuasion and self-suffering can make nonviolence an effective means of resisting injustice. The study also emphasizes the ethical aspects of ahimsa, including its focus on compassion, inner discipline, and the purity of thought and behaviour. Furthermore, the universalism of ahimsa is analysed in terms of how it can be used in many cultural, social, and political situations, making it a pertinent concept for dealing with current world issues. The study makes the case that Gandhian ahimsa overcomes its conventional constraints and provides a comprehensive framework for promoting peace, justice, and human dignity by fusing ethical theory with real-world action. In the end, this research argues that Gandhi’s concept of ahimsa is a living, transformational principle that may direct both individual behaviour and group life in a world that is becoming more complicated and conflict-ridden.